2018
DOI: 10.1038/s41593-018-0094-4
|View full text |Cite
|
Sign up to set email alerts
|

Cortical specialization for attended versus unattended working memory

Abstract: Items held in working memory can be either attended or not, depending on their current behavioral relevance. It has been suggested that unattended contents might be solely retained in an activity-silent form. Instead, we demonstrate here that encoding unattended contents involves a division of labor. While visual cortex only maintains attended items, intraparietal areas and the frontal eye fields represent both attended and unattended items.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
177
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(200 citation statements)
references
References 47 publications
16
177
6
1
Order By: Relevance
“…It is therefore possible that this information is still encoded in the firing rate of neurons, but in a manner not decodable noninvasively (by modulation of neurons in specific ways that do not result in on‐average types of activity measurements). Moreover, in another study using the retro‐cue paradigm, it was observed that while in one area (visual cortex) information about the unattended item disappeared, other higher order cortices (IPS and FEF) continued to maintain this information . This shows that in some brain areas there is no difference in the way attended and unattended information is being maintained.…”
Section: Interactions Between Wm and Long‐term Memorymentioning
confidence: 98%
See 1 more Smart Citation
“…It is therefore possible that this information is still encoded in the firing rate of neurons, but in a manner not decodable noninvasively (by modulation of neurons in specific ways that do not result in on‐average types of activity measurements). Moreover, in another study using the retro‐cue paradigm, it was observed that while in one area (visual cortex) information about the unattended item disappeared, other higher order cortices (IPS and FEF) continued to maintain this information . This shows that in some brain areas there is no difference in the way attended and unattended information is being maintained.…”
Section: Interactions Between Wm and Long‐term Memorymentioning
confidence: 98%
“…Moreover, in another study using the retrocue paradigm, it was observed that while in one area (visual cortex) information about the unattended item disappeared, other higher order cortices (IPS and FEF) continued to maintain this information. 47 This shows that in some brain areas there is no dif-ference in the way attended and unattended information is being maintained. Moreover, in a study where naive monkeys that were never trained on a WM task passively viewed stimuli, persistent stimulus-selective activity was observed in some PFC neurons (but such activity rarely outlasted presentation of the next stimulus).…”
Section: Interactions Between Wm and Long-term Memorymentioning
confidence: 99%
“…In summary, multivariate results show that information about counterfactual outcomes can be decoded in multiple regions of mPFC, although with lower accuracy than for factual ones. As counterfactual outcomes are not relevant for the obtained reward and representational strength is stronger for attended than unattended items (e.g., Christophel et al, 2018), this suggests that they receive less attention.…”
Section: Univariate and Multivariate Effects Of Outcome Valencementioning
confidence: 99%
“…Variability is a fundamental feature of brain activity that is distinct from "randomness" or "noise" (Pinneo, 1966). Neural activity is organized according to structured spatial and temporal profiles (Christophel, Iamshchinina, Yan, Allefeld, & Haynes, 2018;Huth, Heer, Griffiths, Theunissen, & Gallant, 2016;Huth, Nishimoto, Vu, & Gallant, 2012;Luciana, Wahlstrom, Porter, & Collins, 2012). While not always thought of in terms of variability, the fact that spatial and temporal activation patterns within-individuals vary between different psychological processes suggests that variability is a defining feature of brain function (Etzel, Zacks, & Braver, 2013;Patel, Kaplan, & Snyder, 2014).…”
Section: Prior Investigations Of Emotion Regulation Neurodevelopment mentioning
confidence: 99%